Assessment of Left Ventricular Mass and Hypertrophy by Cardiovascular Magnetic Resonance Imaging in Pediatric Hypertension. Issue 10 (14th March 2016) - Supe‐Markovina, Katarina; Nielsen, James C.; Musani, Muzammil; Panesar, Laurie E.; Woroniecki, Robert P.
Abstract : Cardiovascular magnetic resonance (CMR) imaging in adults is considered the gold standard for assessment of left ventricular mass (LVM) and left ventricular hypertrophy (LVH). The authors aimed to evaluate agreement of LVM measurements and LVH determination between echocardiography (ECHO) and CMR imaging in children with hypertension (HTN) confirmed by 24‐hour ambulatory blood pressure monitoring (ABPM). The children (n=22) underwent contemporaneous ECHO, CMR imaging, and ABPM. Patients had a mean body mass index of 30.9±7.5 (kg/m 2 ), and 81.8% had severe HTN. LVM measured by ECHO was 189.6±62.1 g and by CMR imaging was 164.6±44.7 g ( P <.0001). Bland‐Altman analysis revealed significant variability between ECHO and CMR imaging in the measurement of LVM. Interobserver error was higher with ECHO than with CMR imaging. ECHO had high sensitivity and low specificity in LVH determination. In conclusion, ECHO overestimates LVM and is less accurate in measuring LVM as compared with CMR imaging in children with HTN. Further prospective study using CMR imaging to assess LVM in children is warranted.